DIAGNOSTIC ACCURACY OF BEDSIDE INDEX OF SEVERITY IN ACUTE PANCREATITIS (BISAP) SCORE IN PREDICTING OUTCOMES IN PATIENTS PRESENTING WITH ACUTE PANCREATITIS - Fatima, Sarah; Ahmed, Waqas; Akhtar, Khalid Ibrahim; Siddique, Muhammad Khalid; Mushtaq, Rabia; Raza, Syed Muhammad Hashim (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine the diagnostic accuracy of Bedside Index of Severity in Acute Pancreatitis score in predictting outcomes in terms of mortality and severe acute pancreatitis in patients presenting with acute pancreatitis. Study Design: Cross sectional validation study. Place and Duration of Study: Department of Surgery, Combined Military Hospital Malir, from Mar 2019 to Nov 2019. Methodology: A total of 125 patients with the diagnosis of acute biliary pancreatitis were enrolled in the study. Bedside Index of Severity in Acute Pancreatitis score values were worked out for all patients within 24 hours of presentation. The mortality rate and frequency of severe acute pancreatitis was determined. Sensitivity, specificity, negative predictive value, positive predictive value, and diagnostic accuracy of Bedside Index of Severity in Acute Pancreatitis Score was calculated. Results: The mortality rate was 14 (11.2%) and the frequency of severe acute pancreatitis was 41 (32.8%). Bedside Index of Severity in Acute Pancreatitis Score of ≥3 had a sensitivity of 92.86%, specificity of 83.93%, and diagnostic accuracy of 85.6% in predicting mortality in acute pancreatitis. Similarly Bedside Index of Severity in Acute Pancreatitis Score of ≥3 had a sensitivity of 63.41%, specificity of 94.05%, and diagnostic accuracy of 84% in predicting severe acute pancreatitis in patients of acute pancreatitis. Conclusion: Bedside Index of Severity in Acute Pancreatitis Score of ≥3 has a high diagnostic accuracy in predicting severity and is a valuable tool for early assessment of patients with acute pancreatitis.